PENGARUH PENAMBAHAN UBI JALAR TERHADAP KADAR PEROKSIDA PADA MINYAK GORENG BEKAS PAKAI PEDAGANG PECEL LELE DI KELURAHAN TALANG BAKUNG KOTA JAMBI - Dewi Kurniasih; Muslina Muslina; Norma Rotua Simanjuntak (Poltekkes Kemenkes Jambi, 2022)
Background: The use of cooking oil for a long time repeatedly causes the double bond content to be oxidized, forming peroxide groups that can interfere with health and digestion. Yams which contain antioxidants have the ability to break the chain reaction of free radicals. This study aims to determine the effect of adding sweet potato to peroxide levels in used cooking oil used by Pecel Lele Street Food in Talang Bakung Village, Jambi City. Methods: The research method used was a laboratory experiment. The sample in this study was the entire population (total sampling) of 13 used cooking oil obtained from Pecel Lele Street Food in Talang Bakung Village, Jambi City. Peroxide levels (meq O2/kg) will be measured by volumetry-iodometry after soaking in used cooking oil samples with sweet potatoes based on the weight of the sweet potatoes and the soaking time. Results: The results showed that there was an average decrease in the levels of peroxide in used cooking oil added with sweet potatoes and soaked for 1 day 168.154 (meq O2/kg), 2 days 148.568 (Mek O2/kg), 3 days 119.988 (meq O2/kg) and 4 days 70.542 (Mek O2/kg). Based on the weight and length of soaking time, there was an effect of the addition of sweet potato (p-value <0.005) on the peroxide value. Conclusion: The effect of adding sweet potato was based on the weight and length of soaking time on the peroxide value.